PENDIDIKAN ISLAM DAN TRAFIKING - Sulhan, Mohammad (Jurnal Pendidikan Islam, 2016)
The purpose of this study explore the prophetic value of Islamic education in tackling trafficking. This research method is a survey in Cirebon and Indramayu against trafficked women. Islamic education contribute prophetic value in addressing trafficking in terms of; first, to identify the source of the problem. If the problem is poverty and low education, it is necessary to adopt policies to encourage the provision of Islamic education. The government is obliged to protect the welfare of the people persecuted and create; secondly, make regulations in favor of workers, especially women who are vulnerable to trafficking victims. The trick, the government should seriously implement the Presidential Decree No. 88/2002 on the National Action Plan for the Elimination of Trafficking in Women and Children and urged Parliament to back-up the provision of sanctions through Law Crime of Trafficking in Persons. Third, encourage the participation of the clergy to be involved in the response to trafficking through the non-formal Islamic education such as sermons, lectures or fatwa.